Msme Financing Strategy In Improving Customer Business In The Time Of Covid 19 (Case Study At PT. Bank Sumut Syariah Sibolga Branch) - Lestari, sry; Hasibuan, Abdul Naser; Sihotang, Mislawati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The development of a business will help overcome the unemployment problem, given the large number of MSMEs in this country, so that it can increase job opportunities and opportunities to open businesses, which in turn encourages regional and rural development. One of the objectives of sharia microfinance for the economic development of the community is by providing financing capital to customers to develop businesses that aim to manage mitigation. This type of research is a qualitative research, in descriptive form. Sources of data used are primary and secondary data sources. Data was collected using interview, documentation, and observation techniques. The results of this study conclude that the MSME financing strategy in increasing customer business during the covid 19 period uses a murabahah contract in the MSME financing strategy, namely banks must manage mitigation appropriately and banks must focus on industries that have prospects to be financed. during the Covid 19 period in developing business, there was a rapid decline so that it affected the decline in income for several customer businesses that had done MSME financing at PT. Bank of North Sumatra Sibolga Sharia Branch. This is different from before the Covid 19 period, which is happening now, the development of the customer's business is still developing.